Prevalence of endodontic retreatments at the UFCG Dentistry school clinic (Research, Society and Development, 2022)
The endodontic treatment has success rates greater than 90%. However, bacterial factors and anatomical changes can lead to treatment failure. Given the need for a new intervention, several options can be considered, including endodontic retreatment. The fact is that most undergraduate students don’t routinely face this situation during consultations at the UFCG (Universidade Federal de Campina Grande), in the Clinic School of Dentristry (CSD), which can generate insecurity if this procedure is necessary. The objective of this study was to evaluate the prevalence of endodontic retreatments performed at the CSD. This is a cross-sectional, observational study, with a quantitative approach and a data collection procedure, adopting as a data collection strategy the documental analysis of the institution's patient records. The sample consisted of 3811 medical records, of which only 9 (0,31%) referred to endodontic retreatments performed at the CSD and 28 (0,73%) corresponded to indications for retreatments to be performed at other institutions. Of the 9 medical records that constituted the final study population, 6 (66,67%) were female. Of the elements that were portrayed, the lower left lateral incisor and the upper left canine had a higher incidence. Therefore, the rate of retreatments in the CSD is low, which leads us to think that the endodontic treatments performed on site were successful, making it necessary to study the possibility of performing endodontic retreatments in elements with more than one root.